PENGARUH PEMBERIAN MAKANAN TAMBAHAN TERHADAP KONSUMSI ENERGI DAN PROTEIN IBU HAMIL - V. Prihananto; Ahmad Sulaeman; Hadi Riyadi; Nur Heni Sri Palupi (Food and Nutrition Society of Indonesia, 2007)
The objective of this study was to analyze the effect of supplementary foods on pregnant mothers’ energy and protein consumtion. This study was conducted in three sub-districts i.e.: Leuwiliang, Leuwisadeng and Ciampea. The 140 pregnant mothers from these sub-districts were selected for this study. Out of 140 pregnant mothers, 70 pregnant mothers were selected to receive supplementary foods for 6 month and 70 pregnant mothers did not receive any experimental food (control). Product selected as intervention consists of vermicelli, milk, and biscuit. The results of the study showed intervention could improve energy protein consumption of pregnant mothers